Bio-immunization to combat Banana Fusarium wilt tropical race 4 - Damodaran, T; Rajan, S; Mishra, Maneesh; Ramgopal, Ramgopal; Sharma, P C (Indian Horticulture, 2022)
In vitro Bio-immunization technology is a novel tissue culture technology for production of Fusarium wilt disease tolerant plants of banana. The process includes engineering the biomolecule into the banana tissue culture plantlets during in vitro organogenesis phase. Field studies conducted in the hot spot regions of Fusarium wilt at Ayodhya district in Uttar Pradesh and Kattihar district of Bihar revealed that Bio-immunized plantlets were able to sustain the disease incidence to about 98% for a period of 9 months after planting and 85% till harvest.